Prevention of work‐related musculoskeletal disorders in a chemical plant in Taiwan and a comparison of three assessment tools. Issue 5 (19th April 2018) - Chao, Chin‐Jung; Chen, Ming ‐ Chun; Yau, Yi‐Jan
Abstract: Work‐related musculoskeletal disorders (WMSDs) caused by a poor working environment or an improper work design are the most common occupational diseases seriously affecting workers' health, causing huge economic losses in many countries. Thus, the prevention of WMSDs is considered a priority issue worldwide. In this study, three ergonomics analysis tools and a statistic analysis were used to assess the risk level of exposure to WMSDs and to find improvements for the operations in a chemical plant. The applicability of these tools was also evaluated. Results of the analysis suggest that, to greatly prevent the incidence of WMSDs, a mobile elevating platform should be adopted to adjust the handling height of material bags at 90 cm, allowing the operators to stand in front of them to hold their short or long sides. Among the tools, key indicator methods–manual handling operation methods (KIM‐MHO) have the highest sensitivity.